Ticagrelor or prasugrel for patients with acute coronary syndrome treated with percutaneous coronary intervention: A prespecified subgroup analysis of a randomized clinical trial - Coughlan, J. J.; Aytekin, Alp; Lahu, Shqipdona; Ndrepepa, Gjin; Menichelli, Maurizio; Mayer, Katharina; Wohrle, Jochen; Bernlochner, Isabell; Gewalt, Senta; Witzenbichler, Bernhard; Hochholzer, Willibald; Sibbing, Dirk; et al. (JAMA Cardiology, 2021)
Importance: It is unclear whether ticagrelor or prasugrel hydrochloride is superior for patients with acute coronary syndrome (ACS) treated with percutaneous coronary intervention (PCI). Objective: To assess the safety and efficacy of ticagrelor vs prasugrel for patients with ACS treated with PCI. Design, Setting, and Participants: A prespecified analysis was performed of a postrandomization subgroup of 3377 patients who presented with ACS and were treated with PCI in the investigator-initiated, multicenter, phase 4, open-label Intracoronary Stenting and Antithrombotic Regimen: Rapid Early Action for Coronary Treatment 5 randomized clinical trial, conducted from September 1, 2013, to February 28, 2018. Statistical analysis was performed from September 1, 2020, to January 30, 2021. Analysis was performed according to the intention-to-treat principle. Interventions: Patients were randomly assigned to a ticagrelor-based or prasugrel-based strategy. This analysis focuses on the subgroup of patients who underwent PCI that was formed after randomization. Main Outcomes and Measures: The primary end point was a composite consisting of all-cause death, myocardial infarction, or stroke at 12 months. The safety end point was Bleeding Academic Research Consortium (BARC) type 3 to 5 bleeding. Results: The ticagrelor group comprised 1676 patients (1323 men [78.9%]; mean [SD] age, 64.4 [12.0] years), and the prasugrel group comprised 1701 patients (1341 men [78.8%]; mean [SD] age, 64.7 [12.0] years). The primary end point occurred for 162 patients (9.8%) in the ticagrelor group and 120 patients (7.1%) in the prasugrel group (hazard ratio [HR], 1.41; 95% CI, 1.11-1.78; P =.005). Myocardial infarction occurred in 88 patients (5.3%) in the ticagrelor group compared with 55 patients (3.8%) in the prasugrel group (HR, 1.67; 95% CI, 1.19-2.34; P =.003). The safety end point, BARC type 3 to 5 bleeding, occurred in 84 of 1672 patients (5.3%) in the ticagrelor group and 78 of 1680 patients (4.9%) in the prasugrel group (HR; 1.10; 95% CI, 0.81-1.50; P =.54). Conclusions and Relevance: Among patients presenting with ACS who were treated with PCI, the incidence of the primary composite end point occurred less frequently for patients who received prasugrel compared with those who received ticagrelor. The incidence of bleeding events was comparable between the 2 groups. These results suggest that, for patients presenting with ACS who undergo PCI, a prasugrel-based strategy is superior to a ticagrelor-based strategy. However, because these observations are based on a postrandomization subgroup, these findings should be regarded as hypothesis generating and dedicated randomized clinical trials may be warranted to confirm these findings. Trial Registration: ClinicalTrials.gov Identifier: NCT01944800.
CRIS-Team Scopus Importer:2023-03-08